The Effects of Community Characteristics on Solid-Waste Generation and Management in the Village (A Case Study: Kurandak, North Sumatra) - Wisnu Prayogo; Royana Chairani; Desy Rahmadani Telaumbanua; Novi Fitria; Firdha Cahya Alam; Muhammad Faisi Ikhwali; Rifka Noor Azizah; Istiqomah Shariati Zamani (Universitas Diponegoro, 2022)
Waste is a very complex and urgent problem to be solved. The problems occur due to the participation of the residents as the leading actor. This study aimed to determine the significance of the influence of gender, age, education, employment status, income, duration of stay, and the level of knowledge on waste generation and management. Respondents to questionnaires and interviews were 37 people whose numbers were determined based on the Slovin equation, while data was analyzed using SPSS Statistics 20 software. A person's educational status significantly positively affects people's habits in reducing waste generation. The following positive significance was income, gender, and length of stay. Age and employment status have a negative correlation, indicating that the older and working, the less waste the society generates. Besides affecting waste generation, it turned out that education also significantly affects waste management. Therefore, education is the main factor considered in waste planning. The results of this study can be used as input for the Indonesian Government in providing information through training and the provision of waste management facilities.